Pengaruh Bahasa Gaul Terhadap Penggunaan Bahasa Indonesia di Kalangan Gen Z - Halimatussyakdiah Siregar; Qori Afifah Tampubolon; Dewi Ribreka; Osmondo Jorey Pratama; Lili Tansliova (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
In this study, quantitative methods using structured questionnaires were used to assess the impact of slang use on good and correct Indonesian use among Generation Z. The study participants consisted of 35 people from Generation Z. Data analysis concluded that although the majority of respondents admitted to using slang in daily life, awareness of the importance of using Indonesian formal language still remained high. The results showed that the use of slang did not have a significant effect on the participants' ability to use Indonesian words accurately. This highlights that although Gen Z generally embraces slang culture, Indonesian is still considered important in the context of communication. Therefore, continuous efforts are needed to encourage the use of Indonesia's official language in various communication situations. Therefore, continuous efforts are needed to encourage the use of Indonesia's official language in various communication situations. A follow-up study examined the impact of slang use on Generation Z's interpersonal and professional communication, and highlighted that although slang has an interesting cultural influence, awareness of formal language use remains relevant.